Spillover from the Conflict in Syria An Assessment of the Factors that Aid and Impede the Spread of Violence - Young, William (Research Reports, 2014)
Aid flowing into Syria is intended to determine the outcome of the conflict between rebel factions and Damascus. Instead, it could perpetuate the civil war and ignite larger regional hostilities that could reshape the political geography of the Middle East. This report examines the main factors likely to contribute to or impede the spread of violence from civil war and insurgency in Syria, and then examines how they apply to neighboring states.